A decade-long analysis of 98 chronic myeloid leukemia patients: Laboratory data and clinical progress at a single center - Nabihah Mohd Shakri; Razan Hayati Zulkeflee; Mohd Nazri Hassan; Sinari Salleh; Nur Aini Shakirah Ahmad Shuyuti; Marini Ramli; Azlan Husin; Abu Dzarr Abdullah (Iraqi Journal of Hematology)
BACKGROUND: Chronic Myeloid Leukemia (CML) is a myeloproliferative neoplasm characterized by the presence of the Philadelphia chromosome (BCR-ABL1 fusion gene). CML primarily progresses through chronic, accelerated, and blast phases. While global studies on BCR-ABL1 fusion transcript types and their associations with clinical, laboratory, and prognostic profiles exist, such data is scarce in Malaysia. OBJECTIVES: This study aimed to determine the distribution of BCR-ABL1 fusion transcript types and evaluate their associations with demographic, clinical, laboratory, prognostic profiles, and disease outcomes among Malaysian CML patients. PATIENTS, MATERIALS AND METHODS: A total of 98 patients diagnosed with CML were identified at East Coast Hospital, Malaysia. This 12-year cross-sectional study was carried out using data extracted from patients’ medical records. Molecular results for BCR-ABL1 fusion genes were obtained using one-step multiplex reverse transcriptase polymerase chain reaction. RESULTS: Out of the 98 patients, 56% had e14a2, 41% had e13a2 fusion transcripts, while the remaining 2 patients had e14a3 transcripts. Additionally, 1 patient co-expressed both e13a2 and e14a2. Among patients with the major BCR-ABL1 transcript type, those with e14a2 fusion transcripts showed an older median age (P = 0.025), while patients with e13a2 fusion transcripts had significantly higher white blood cell (WBC) counts (P = 0.014). Furthermore, there were significantly more patients with blastic transformation in the e13a2 group (P = 0.038). The median latency period of CML was 12 months. The blast cell lineages consisted of myeloid (68.4%), followed by B-lymphoid (26.3%) and mixed phenotypic (5.3%). The differences in fusion transcript expression might influence certain parameters; for instance, older patients were associated with the e14a2 fusion transcript. Meanwhile, patients exhibiting e13a2 might have a higher WBC count at diagnosis and be more vulnerable to blastic transformation of CML. CONCLUSIONS: This study highlights the predominance of e14a2 fusion transcripts in Malaysian CML patients and its association with older age. The e13a2 transcript was linked to higher tumor burden and a higher rate of blastic transformation, suggesting potential prognostic significance. These findings underscore the importance of baseline molecular profiling for optimizing disease management.